2010
DOI: 10.17705/1jais.00224
|View full text |Cite
|
Sign up to set email alerts
|

The Social Shaping of Packaged Software Selection

Abstract: As organisations increasingly engage in the selection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 103 publications
(131 reference statements)
2
37
0
Order By: Relevance
“…We therefore propose that future research adopt a multistakeholder perspective and evaluate differences in stakeholder perceptions. This suggestion is consistent with recent calls for research on CC, ITO, and packaged software acquisition Howcroft and Light, 2010;Bidwell, 2012). Table 5 summarizes our discussion and proposes future research directions.…”
Section: Implications For Researchsupporting
confidence: 88%
“…We therefore propose that future research adopt a multistakeholder perspective and evaluate differences in stakeholder perceptions. This suggestion is consistent with recent calls for research on CC, ITO, and packaged software acquisition Howcroft and Light, 2010;Bidwell, 2012). Table 5 summarizes our discussion and proposes future research directions.…”
Section: Implications For Researchsupporting
confidence: 88%
“…The study also confirms the appropriateness of investigating cognitive frames to understand how the beliefs and scripts of organizational actors facilitate or hinder the enactment of organizational actions for the achievement of organizational goals (Argyris & Schon, ; Howcroft & Light, ). It revealed that academic librarians' professional frames, beliefs, and scripts for library activities are critical factors in IR innovation and implementation initiatives.…”
Section: Discussion Of Research Findingssupporting
confidence: 71%
“…The SST approach has been shown to be useful in making sense a wide range of artefacts. Previous studies for instance have examined refrigerators, missile guidance systems, electric lighting, the bicycle, the telephone and videotext, radio, telephony, and electric media and computing and organisational technologies (see (MacKenzie and Wajcman 1985, Bijker 1987, Bijker and Law 1994, Bijker 1995, Abbate 1999, Mackenzie and Wajcman 1999, Oudshoorn and Pinch 2005, Pinch 2005, Light and Wagner 2006, Boczkowski and Lievrouw 2008, Howcroft and Light 2010, Lauer 2012). It has been suggested that historians and sociologists of technology have focused on technology as their major topic of analysis, whereas those who do cultural and media studies have primarily attended to users and consumers Pinch 2005, Flanagin et al 2010).…”
Section: Theorising Technological Appropriation Introductionmentioning
confidence: 99%